In-Situ Measurement of Gas Permeability for Membranes in Water Electrolysis - Shuaimin Li; Chuan Song; Li Xu; Yuxin Wang; Wen Zhang (Membranes)
Water electrolysis (WE) is a green technology for producing hydrogen gas without the emission of carbon dioxide. The ideal membrane materials in WE should be capable of transporting ions quickly and have gas barrier properties in harsh work environments. However, currently, no desirable measurement method has been developed for evaluating the gas barrier behavior of the membranes. Hence, an in-situ electrochemical method is developed to measure the gas permeability of membranes in the actual electrolysis environment, with the supersaturated state of H2 in the electrolyte and H2 bubbles during the electrolysis process. Four membranes, including Zirfon (a state-of-the-art alkaline WE membrane), polyphenylene sulfide fabric (PPS, a commercial alkaline WE membrane), FAA-3-PK-75 (a commercial anion-exchange membrane), and BILP-PE (a home-made composite membrane) were employed as the standard samples to perform the electrochemical measurement under different current densities, temperatures, and electrolyte concentrations. The results show that an increase in electrolytic current density or temperature or a decrease in KOH concentration can increase the H2 permeability of the membrane. The two porous membranes, Zirfon and PPS, are more affected by the current density and KOH concentration, while the dense FAA-3-PK-75 and BILP-PE membranes have a stronger ability to hinder H2 permeation. Under the conditions of 80 °C, 30 wt.% KOH, 101 kPa, and 400 mA·cm−2, the hydrogen permeability (×1010 L·cm·cm−2·s−1) of Zirfon, PPS, FAA, and BILP-PE are 263, 367, 28.3, and 5.32, respectively.